Pengaruh Unggahan Akun Instagram @Official.Unsika terhadap Pemenuhan Kebutuhan Informasi Mahasiswa FISIP UNSIKA - Yulianti, Sindy Sri; Utamidewi, ⁠Wahyu; Muslimah, Tikka (Innovative: Journal Of Social Science Research, 2025)
The research is motivated by the development of social media which has now become an important tool in disseminating information in the academic environment. UNSIKA utilizes Instagram through the @official.unsika account as an official channel for delivering information to students. Academically, FISIP students are generally equipped with an understanding of communication theory, mass media, and the dynamics of public information. This makes FISIP students a group that is more sensitive to the use and function of social media as an institutional information channel. The purpose of this study is to determine the extent to which the uploads of the @official.unsika Instagram account affect the fulfillment of the information needs of FISIP UNSIKA students. Researchers use quantitative methods using a descriptive statistical approach. The technique used in sampling is cluster sampling technique with a total of 94 respondents. Researchers use the theory of uses and gratifications. The results of the study indicate that sub-variable X, namely duration and attention, has a significant effect on fulfilling students' information needs, while sub-variable X, namely frequency, has no significant effect on fulfilling the information needs of FISIP UNSIKA students.